Опыт применение метода управления по целям МВО на современном предприятии - Тешабаев, А. Э (Видавництво НГУ, 2014)
В статье описан опыт применения метода Управления по целям – Management by Objective (MBO) на крупном современном предприятии и проблемы внедрения, его преимущества и условия необходимые для эффективного применения.

Article describes the experience of implementation and usage of MBO -Management by Objective on large modern industrial company, problems of implementation, achievements and conditions for successful usage of method.
Implementation and using mbo – management by objective in large modern company
Keywords: Управление по целям – Management by Objective (MBO); цели; мотивация персонала; решение проблем; Management by Objective (MBO); goals and objectives; motivation of employee; problem-solving